(untitled) (Annals of Medical Research, 2024)
Aim: Penetrating traumas (PT) in children, caused by firearms or cut/pierce instruments, are relatively rare, accounting for 10-20% of pediatric traumas. These traumas are serious and can lead to significant consequences, hence the need for prompt and multidisciplinary management [1-4]. Materials and Methods: The study is a retrospective analysis of pediatric patients treated for PT in the pediatric intensive care unit (PICU). Patients were divided into two groups based on the cause of injury: cut/pierce instrument wounds and firearm wounds. Data collected included age, gender, diagnosis at PICU admission, type of trauma, cause of trauma (assault, suicide), vital signs, nature of trauma (thoracic, abdominal, cranial, extremity), associated organ failures, surgical needs, performed surgeries or procedures, need for respiratory and cardiovascular support, transfusion requirements, lab parameters (blood gases and organ functions), Pediatric trauma score (PTS) , Pediatric Risk of Mortality (PRISM) score, PICU stay duration, and outcomes. Results: Between April 2022 and November 2023, a total of 425 pediatric cases were treated for trauma in the PICU, with a 6% frequency of PT. The majorities of PT cases were in the adolescent age group and were male (76%). The cause of PT was violence in 88% (22/25) cases and attempted suicide in 12% (3/25) cases. 72% were caused by cut/pierce objects and 28% were caused by firearm wounds. The location of trauma was thoracic in 48% (12/25), abdominal in 44% (11/25), thoraco-abdominal in 4% (1/25), and lower extremity in 4% (1/25). There was no cranial penetrating trauma. However, there was no vascular injury in any of the cases, despite damage to extremities near major arteries. In most cases (19/25, 76%), thoracic and/or abdominal surgery, including tube thoracostomy, was required to treat hemopneumothorax. Blood transfusion was performed in 52% of the cases (13/25). Five cases required non-invasive mechanical ventilation, and one case required mechanical ventilation. The cases were hospitalized in the PICU for a mean period of 3.7 days. The mean PTS score was 6.2±1.4 (range: 2-8), and the mean PRISM score was 10.9±3.7 (range: 7-37). All cases were discharged. There were no deaths. Conclusion: Penetrating traumas are rare in children but can lead to serious consequences. Therefore, a rapid and multidisciplinary approach is vital in the management of PT cases in children.